SIKAP TOLERANSI UMAT BERAGAMA DI DESA GUDO KABUPATEN JOMBANG - Agus Miftakus Surur; Sofi Nuril Fu’ad; M. Machrus ‘Arif; Sahrul Setiawan; M. Sultan Almustafa Kawakib; Tahta Egit Prakoso (IAIN Kediri, 2018)
The community of the District of Gudo in Jombang Regency applies the limits of interaction in relations between religions, especially in terms of worship. This happened because there were still some people who invited other religious people to attend their worship services and the target of their teachings was children from outside their religion. Therefore, the community is worried that the young children will be indoctrinated by the teachings of other religions. This study uses a qualitative approach that aims to determine the attitude of tolerance of religious people in the grassroots region. With this qualitative approach, this research is more directed at direct observation. From each religion in Gudo has an opinion about tolerance: 1) Confucianism believes tolerance is a respect between one religion and another. 2) Christianity believes tolerance is a feeling of love and mutual trust between religious people. 3) Islam believes that tolerance is a freedom of life that has limitations, namely their own religion.Keywords: Tolerance, diversity, harmony